No Arachnoid Granulations—No Problems: Number, Size, and Distribution of Arachnoid Granulations From Birth to 80 Years of Age - Radoš, Milan; Živko, Matea; Periša, Ante; Orešković, Darko; Klarica, Marijan (Frontiers in Aging Neuroscience, 2021)
Introduction: The study aims to quantify changes in the number, size, and distribution of arachnoid granulations during the human lifespan to elucidate their role in cerebrospinal fluid physiology. Material and methods: 3T magnetic resonance imaging of the brain was performed in 120 subjects of different ages (neonate, 2 years, 10 years, 20 years, 40 years, 60 years and 80 years) all with the normal findings of the cerebrospinal fluid system (CSF). At each age, 10 male and 10 female subjects were analyzed. Group scanned at neonatal age were re-scanned at the age of two, while all other groups were scanned once. Arachnoid granulations were analyzed on T2 coronal and axial sections. Each arachnoid granulation was described concerning size and position relative to the superior sagittal, transverse and sigmoid sinuses and surrounding cranial bones. Results: Our study shows that 85% of neonates and two-year-old children do not have visible arachnoid granulations in the dural sinuses and cranial bones on magnetic resonance imaging. With age, the percentage of patients with arachnoid granulations in the superior sagittal sinus increases significantly, but there is no increase in the sigmoid and transverse sinuses. However, numerous individuals in different age groups do not have arachnoid granulations in dural sinuses. Arachnoid granulations in the cranial bones are found only around the superior sagittal sinus, for the first time at the age of 10, and over time their number increases significantly. From the age of 60 onwards, arachnoid granulations were more numerous in the cranial bones than in the dural sinuses. Conclusion: The results show that the number, size, and distribution of arachnoid granulations in the superior sagittal sinus and surrounding cranial bones change significantly over a lifetime. However, numerous individuals with completely normal CSF system do not have arachnoid granulations in the dural sinuses, which calls into question their role in CSF physiology. It can be assumed that arachnoid granulations do not play an essential role in CSF absorption as it is generally accepted. Therefore, the lack of arachnoid granulations does not appear to cause problems in intracranial fluid homeostasis.